Health Promoting Lifestyle Profile Among University Students and its Relation with the Study Speciality (Epidemiology, Biostatistics, and Public Health, 2025)
Introduction Unhealthy lifestyle behaviours are common modifiable risk factors for NCDs which cause a great decline for age group suffering from chronic diseases. The university years serve as a particularly crucial and formative stage for the overall development of lifelong behaviours that can either promote or seriously impair health outcomes. We aimed to assess health promoting lifestyle profile among university students and detect its determinants. Methodology Across-sectional study was conducted among 397 students (204 medical and 194 non-medical) using HPLP-II questionnaire. Results 75.82% of students were females and 96.22% were non-smokers. Less than half (43.3%) of students achieved total score of HPLP-II higher than 2.5. Medical students reported significant lower median total scores than non-medical ones (median:2.38 vs. 2.5 respectively). They also achieved significant lower median health responsibility (median 2 vs. 2.22) and nutrition (median 2.22 vs. 2.33) subscales compared to non-medical. Conclusion the higher burden that medical students face is responsible for the worse lifestyle scores they report. Intervention programs should be carried out to enhance lifestyle behaviours among the whole university students with special attention to medical ones.
Keywords: health-promoting lifestyle; HPLP-II; medical; non-medical university students